Molecular mechanisms of synaptogenesis - Qi, Cai; Luo, Li-Da; Feng, Irena; Ma, Shaojie (Frontiers in Synaptic Neuroscience, 2022)
Synapses are the basic units for information processing and storage in the nervous system. Only when the synaptic connection is established, it is meaningful to discuss the structure and function of a circuit. In addition, the unparallel cognitive ability of human is correlated with increase in the number of synapses, whereas genes involved in synaptogenesis are also frequently associated with neurological or psychiatric disorders, suggesting strong connections between synaptogenesis and brain physiology or pathology. Thus, understanding the molecular mechanisms of synaptogenesis is the key to the myth of circuit assembly and neural computation. Besides, it will provide therapeutic values for the treatment of neurological disorders. Multiple molecular events must coordinate precisely to generate a synapse. To understand the molecular mechanisms underlying synaptogenesis, we need to know the molecular components of synapses, how these molecular components are held together and how the molecular networks are refined underlying neural activity to generate new synapses. Thanks to the intensive investigations from this field, our understandings of synaptogenesis have progressed significantly. Here, we will review the molecular mechanisms of synaptogenesis by going over the studies on the identification of molecular components in synapses and their functions in synaptogenesis, how cell adhesion molecules connect these synaptic molecules together and how neural activities mobilize these molecules to generate new synapses. In addition, we will summarize research of human specific regulatory mechanisms on synaptogenesis as well as results from human genetics studies on synaptogenesis and brain disorders.